Zmartwychwstanie ciała według Tertuliana - Wysocki, Marcin 1975- (2009)
Resurrection was one of the most important themes in the writings of Tertullian (ca 150 - 220), who is called sometimes "theologian of the hope". Presented paper presents teaching of the first theologian of the West on resurrection of the body. In the article's first part the historical (i.e. persecutions and believes in resurrection before Tertullian) and doctrinal background (heresies) of his works on the resurrection is shown, than - in the next section - vocabulary, which were used by Tertullian to describe phenomenon of the resurrection. In the forth part author presents the main points of Tertullian's view of resurrection of the body. In the fifth chapter connections between resurrection and martyrdom are presented.
Keywords: ciało; zmartwychwstanie; Tertulian; ciało